Numerical investigation of heat transfer in thermosyphon under the emergency mode of operation of lithium-ion batteries of aircraft; MATEC Web of Conferences; Vol. 141 : Smart Grids 2017 - Krasnoshlykov A. S. Aleksandr Sergeevich (2017, 2017)
Title screen